2017
DOI: 10.1016/j.reprotox.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vascular disruptor compounds by analysis in zebrafish embryos and mouse embryonic endothelial cells

Abstract: To identify vascular disruptor compounds (VDCs), this study utilized an in vivo zebrafish embryo vascular model in conjunction with a mouse endothelial cell model to screen a subset of the U.S. Environmental Protection Agency (EPA) ToxCast Phase I chemical inventory. In zebrafish, 161 compounds were screened and 34 were identified by visual inspection as VDCs, of which 28 were confirmed as VDCs by quantitative image analysis. Testing of the zebrafish VDCs for their capacity to inhibit endothelial tube formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 65 publications
1
26
0
Order By: Relevance
“…However, the compound is potent for developmental toxicity, causing severe malformations in the low micromolar range. A lack of angiogenic inhibition coupled with embryotoxicity was also noted in a separate zebrafish study following developmental exposure to 5HPP-33 [26]. These data indicate that 5HPP-33 may be developmentally toxic in zebrafish via mechanisms other than angiogenic inhibition.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, the compound is potent for developmental toxicity, causing severe malformations in the low micromolar range. A lack of angiogenic inhibition coupled with embryotoxicity was also noted in a separate zebrafish study following developmental exposure to 5HPP-33 [26]. These data indicate that 5HPP-33 may be developmentally toxic in zebrafish via mechanisms other than angiogenic inhibition.…”
Section: Discussionsupporting
confidence: 56%
“…These data indicate that 5HPP-33 may be developmentally toxic in zebrafish via mechanisms other than angiogenic inhibition. A recent publication showed that 5HPP-33 directly binds tubulin and disrupts microtubule dynamics during cellular mitosis [37] providing a mechanistic possibility for the widespread teratogenicity observed in the current study and McCollum et al [26]. Similar to 5HPP-33, a total of 14 of 29 chemicals that were negative for vascular toxicity caused malformations in zebrafish, including compounds like bisphenol AF, 4-nonylphenol, octyl gallate, and perfluorooctanesulfonic acid that were highly ranked by the predictive signature.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…ToxCast highthroughput screening (HTS) data for 25 assays mapping to targets in embryonic vascular disruption signature [Knudsen and Kleinstreuer, 2011] were used to rank-order 1060 chemicals for their potential to disrupt vascular development. The predictivity of this signature is being evaluated in various angiogenesis assays, including tubulogenesis in endothelial cells from zebrafish, chick, mouse and human species Vargesson et al 2003;Knudsen et al 2016;McCollum et al 2016;Nguyen et al 2016].…”
Section: How It Is Measured or Detectedmentioning
confidence: 99%